Optimization of Frequency and Stirring Rate for Synthesis of Magnetite (Fe3O4) Nanoparticles by Using Coprecipitation- Ultrasonic Irradiation Methods. (2017) - Rahmawati, Retno; Permana, Mohammad Gilang; Harison, Bill; Nugraha; Yuliarto, Brian; Suyatman; Kurniadi, Deddy
Abstract: Magnetite (Fe3 O4 ) nanoparticles from iron sand as starting materials have been successfully synthesized by using coprecipitation- ultrasonicirradiation methods. This paper reports the preparation and optimization result of ultrasonic frequency and stirring rate during the synthesis process. The frequencies of ultrasonic conducted in this research are 300, 400 and 400 kHz. The stirring rates performed in the synthesis process are varied from 500 to 900 rpm. The qualitative analysis by using X-Ray Diffractometer (XRD) showed that the structure of Fe3 O4 nanoparticles have a same phase with ICCD No. 75-0449. Moreover, the quantitative analysis by using Debye-Scherer equation showed that the crystallite size of Fe3 O4 ranging from 21 to 25 nm depend on the ultrasonic frequency and stirring rate. Meanwhile, the transmission electron microscopy (TEM) result revealed that the Fe3 O4 tend to form spherical shape with little agglomeration on the morphology of the Fe3 O4 . The magnetic properties of Fe3 O4 were investigated by using vibrating sample magnetometer (VSM). The VSM measurement result showed that the Fe3 O4 have saturation magnetization (Ms), remanent magnetization (Mr) and coercivity field (Hc) at 25 emu/gram, 6, 0562 emu/gram, and 0, 0108 T, respectively. Based on the magnetic characterization, the Fe3 O4 nanoparticles have a potential to be appliedin biomedical field.